Cryopreservation of Dendrobium shavin white using sucrose preculture - encapsulation vitrification method - Nagappan, Pugalanthi (2015)
Dendrobium Shavin White is a hybrid from the crossing between Dendrobium Walter Oumae and Dendrobium Queen Florist which has vigorous growth and durable. Dendrobium Shavin White produces flowers all year around with high number of flowers in a single inflorescence. The bloom is usually greenish white. PLB, the somatic embryo of orchid is one of the tissues with high ability to become plantlets when cultured. Growth and development of PLBs cannot be arrested due to active cellular divisions. Therefore a suitable protocol to preserve the PLBs is required for efficient handling of the planting material. This experiment is conducted to determine the survival of naked PLB exposure to different concentrations of sucrose, followed by exposure to PVS2 after encapsulation upon cryopreservation. It is also conducted to determine the survival of encapsulated PLB exposure to different concentrations of sucrose, followed by exposure to PVS2 upon cryopreservation. Prior to cryopreservation of PLBs, viability test was carried out. The experimental design used was CRD with 4 replications. Data collected were percentages of PLBs regeneration and colour of PLBs. Data show that, the highest survival percentage of PLBs in LN was recorded by encapsulated PLB pre treated with 0.2 M sucrose concentration in 15 minutes soaking of PVS2 (31.25%).